Studi Etnografi Suku Baduy: Pengembangan Produk Lokal dan Olahraga Tradisional Terintegrasi Android dalam Meningkatkan Ekonomi Masyarakat Baduy dan Motivasi Olahraga - Nugrahani Febrina Sari; Elsa Ariestika; Hazrina Amni; Indri Wulandari (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Changes in time and development technology have impact positive. Application android based can become great opportunity​ in maintain existence something region Wrong the only one that is public ethnic group Baduy. 2024 Tourists​ as many as 40,153 people visited to region ethnic group Baduy. Purpose study this that is marketing product local people in the Baduy tribe​ through android applications that can accessible. Method research used​ that is study and development Where adoption model development using a waterfall model consisting of from stages analysis need, design system, implementation, and testing stage​ testing this androidapps rated by IT experts use test testing box black, and done test try field through respond traveler and respond public local customs Baduy. Results analysis use questionnaire scale linkert and respond determine level Agreement to something statement with choose available options​ with slaka 1-5. Results percentage by 86.5% through criteria interpretation score of the 30 respondents included in category very Good and product the worthy used. Application with title namely